2018
DOI: 10.1038/s41366-018-0111-4
|View full text |Cite
|
Sign up to set email alerts
|

Is leptin resistance the cause or the consequence of diet-induced obesity?

Abstract: A pre-existing reduction in leptin sensitivity determines the susceptibility to develop excessive DIO after fcHFHS diet exposure. Rats with a pre-existing reduction in leptin sensitivity develop excessive DIO without eating more calories or altering their leptin sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 46 publications
2
32
2
1
Order By: Relevance
“…Interestingly, baseline leptin sensitivity on a CD, although not total caloric intake or differences in diet component preference, predicted subsequent weight gain when switched to a fc-HFHS diet. 40 In contrast to the rapid onset of leptin unresponsiveness observed in one study after 7 days of fc-HFHS diet, 34 we now observed leptin resistance after 28 but not 14 days of fc-HFHS diet consumption. 40 These differences might be explained by different methodology.…”
Section: Leptin Dynamics and Neuroinflammationcontrasting
confidence: 65%
See 4 more Smart Citations
“…Interestingly, baseline leptin sensitivity on a CD, although not total caloric intake or differences in diet component preference, predicted subsequent weight gain when switched to a fc-HFHS diet. 40 In contrast to the rapid onset of leptin unresponsiveness observed in one study after 7 days of fc-HFHS diet, 34 we now observed leptin resistance after 28 but not 14 days of fc-HFHS diet consumption. 40 These differences might be explained by different methodology.…”
Section: Leptin Dynamics and Neuroinflammationcontrasting
confidence: 65%
“…Consumption of a fc-HFHS, for up to 6 months, increases total body weight gain compared to CD controls, and this was associated with profound increases in abdominal and subcutaneous white adipose tissue (WAT) mass. [33][34][35][36][37][38][39][40][41][42] Male Wistar or Sprague-Dawley rats with access to a fc-HF or fc-HS diet consistently show no or very limited effects on total body weight gain compared to CD controls, despite increases in terminal WAT mass. [33][34][35][36][37] When female Sprague-Dawley rats were maintained on a fc-HFHS diet containing a solution with maltodextrin, a polysaccharide composed of chains of glucose, for up to 36 weeks, increases in body weight gain and persistent hyperphagia were also observed.…”
Section: Effects Of Fc-hfhs Diets On Body Weight and White Adipose mentioning
confidence: 99%
See 3 more Smart Citations